Development of Pseudo-nitzschia species-specific oligonucleotide primers for ribosomal intergenic spacer analysis - Teng, Sing-Tung; Lim, Hong-Chang; Lim, Po-Teen; Leaw, Chui-Pin (Universiti Malaysia Sarawak, 2013)
A study was carried out to determine the community structure of Pseudo-nitzschia species based on ribosomal intergenic spacer analysis (RISA). A molecular approach was carried out by using the secondary structure of the internal transcribed spacers (ITSs) transcripts to characterize the genetic variability of Pseudo-nitzschia species. Clonal cultures used were grown in SWII medium at 26°C under 14: 10 hour light: dark photo cycle. Genomic DNA was extracted and used for ITS region amplification and sequencing. The sequences obtained were used to predict the RNA secondary structure. Sequence-structure alignment was performed with related taxa to identify the sequence signatures. Pseudo-nitzschia species- and genus-specific oligonucleotide primers were designed in silico based on the secondary structure information. The designed specific primers were tested for the development of a genotyping system